جەنگی پیلۆپۆنیزو ڕووخانی ئەسینا (٤٣١ – ٤٠٤ پ.ز) لێكۆڵینەوەیەكی مێژوویی سیاسییە - مستەفا, پ. د. شوان عوسمان; رحيم, حسن علي حميد (Sulaimani Journal for Humanities, 2023)
The Peloponnesian War, the longest internal war in ancient Greek history (431-404 BC). broke out between Athenians and their allies and Sparta and their allies. In the year (431 BC. M) when a war began, Athens was superior in its fleet and navy, while Sparta excelled in its forces The land of the heavy infantry, and therefore the plan of Athens was based not to engage in a land battle against Sparta, while taking refuge behind the walls of the city of Athens and the great walls that protected its ports, Phaleron, from the attacks of Sparta and the Peloponnesian land alliance. Athens was also keen to preserve its naval fleet - the source of its strength - to overwhelm Sparta and its allies when circumstances and the appropriate opportunity arise, all of this was at the behest of the leader Pericles.